History Makers: Pioneers of the American West - Taylor, Sherri Peel; Nang ChanYeema (San Diego CA USA Lucent Books, 2002)
Profiles the lives and sturggles of American pioneers Daniel Boone, Stephen Fuller Austin, Jedediah Smith, John Augustus Sutter, Narcissa Prentiss Whitman, and John Charles Fremont.
Keywords: Adult Nonfiction